The ancient Balkan Illyrian goddess „Virgo paritura" and the Polish lands in the early Iron Age - Szafrański, Włodzimierz (Balcanica Posnaniensia. Acta et studia, 1990)
The article analyzes the problem of the origin and meaning of the iconography of face urns in the Polish lands of the Early Iron Age in the context of Balkan influences. The problem is significant for understanding the transfer of religious ideas and symbolism between southern Europe and the Baltic area. The aim of the work is to demonstrate the role of Illyrian cultural patterns in shaping this iconography. The author applies a comparative analysis of archaeological finds, especially an Illyrian pendant from the 7th–5th centuries BC and representations on Pomeranian urns. The most important results indicate that schematic representations on the urns, previously interpreted differently, in fact correspond to the image of a giving-birth goddess known from Illyrian culture. It has been demonstrated that this motif replaced earlier Etruscan forms of depicting the deceased and was connected with the idea of rebirth and life after death. The analysis of iconography, including “herringbone” motifs and elements such as the horse or solar symbols, confirms their connection with the cult of the goddess of life and death. The conclusion is that the emergence of face urns was the result not only of Etruscan influences but, to a decisive extent, of Illyrian ideological infiltration, which changed their symbolic meaning.